Design and development of suspension system for power generation. (2021) - Shashank, R.; Kashikar, Shashank S.; Sriram, Vishnu; D'Souza, Vivian; Srinivas, R.; Ullegaddi, Manjunath M.; Arun, R.
Abstract: Suspension system in a vehicle provides the framework for the vehicle to nullify the vibrations arising from the roads irregularities by reciprocation of coil springs. Kinetic energy is stored in the springs when reciprocating and the frequency of vibration is attenuated by dampers only to dissipate all the energy in the form of heat. As the quest of green engineering is at its apex, the prototype Suspension System for Power Generation is in conjunction with it while being modest in deisgn and simplistic in functioning. The devised prototype Suspension System uses the energy to generate electricity which is otherwise dissipated. In this work, process of arriving at the fabricated model of Suspension System for Power Generation is elaborated. The preliminary and existing techniques which help in regenerating energy dissipation in suspensions are discussed and the way they led to contrive the concept of prototype Suspension System is elucidated. With the concept, the derivation of specifications and the process of designing the Suspension System is delineated. The Suspension System generated a potential difference in the range of 125 mV to 350 mV.